Geospatial Analysis of Public Water Supply Facilities in Awka Capital Territory, Anambra State Nigeria (Journal of Geography, Meteorology and Environment, 2023)
Functional public water supply scheme remains an integral part of liveable cities. However, access to functional government water supply scheme has remained elusive in several states including Anambra State. Despite successive efforts on the part of government to mitigate associated problems, the results seem not to be evident yet. This paper examined water supply facilities in Awka Anambra State and its geospatial distribution. Percentage, mean and standard deviation were used to analyze data generated from distributed questionnaire. GPS and ArcGIS (version 10.5) were also used for acquiring coordinates and plotting as well. Quadrat analysis and Kolmogorov Smirnov test were used to determine the geographical distribution of water facilities in the area. The results showed that Government water supply facilities were found to be moribund. Residents depend on water vendors for daily supply or resort to personal wells and boreholes amongst other sources. This translates to proliferation of wells and boreholes as well as residents patronizing sources of questionable quality. Government water supply facilities were also found to be randomly distributed but access to its services is found to be lopsided. The implication of this is that some residents have better access to borehole locations than others. The Awka Capital Territory Development Authority (ACTDA) and the Anambra State Physical Planning Board were enjoined to take up the responsibility of ensuring good planning of the water supply facilities to guarantee access to majority of consumers. This paper also suggests proper reticulation be done to ensure water supply to the nooks and crannies of the study area.
Keywords: Water; Water Supply; Awka Capital Territory; Anambra State; Boreholes